2007
DOI: 10.1108/dlo.2007.08121bad.010
|View full text |Cite
|
Sign up to set email alerts
|

Work-based learning in the UK: scenarios for the future

Abstract: A key task of "work-based learning" (WBL) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Another study found that proposed learning in accordance with work policies and linked to EBP in the clinical area results in improve patient care, empowers nurses to change and develop practice [6] and can be viewed as being directly relevant to the nurse. Another study undertaken by, Mohamud et al [7] looked at scenarios created by work-based learning (WBL). It was examined in context of the skills gap.…”
Section: Three Themes Emerged From the Literaturementioning
confidence: 99%
“…Another study found that proposed learning in accordance with work policies and linked to EBP in the clinical area results in improve patient care, empowers nurses to change and develop practice [6] and can be viewed as being directly relevant to the nurse. Another study undertaken by, Mohamud et al [7] looked at scenarios created by work-based learning (WBL). It was examined in context of the skills gap.…”
Section: Three Themes Emerged From the Literaturementioning
confidence: 99%